Pembelajaran melalui Artificial Intelligence, peluang atau hambatan? - hariroh, arin (Maliki Interdisciplinary Journal, 2026)
Artificial Intelligence (AI) has opened up numerous opportunities for transformation in the world of education. This article will discuss how AI can enhance learning methods, personalize materials, and improve the efficiency of educational systems. However, on the other hand, the implementation of AI also presents challenges in the form of technological access gaps, the risk of replacing educators’ roles, and concerns regarding data privacy. Through literature analysis and case studies, this article critically examines whether AI represents an opportunity that fosters innovation in education or rather a barrier that needs to be addressed to ensure effective transformation. This research uses a qualitative approach with a literature review method to identify various AI implementation models in education and their implications for the learning process. The study results indicate that AI has significant potential to increase student engagement, the effectiveness of adaptive learning, and the efficiency of educational management. However, AI implementation also requires digital infrastructure readiness, improved educator competency, and clear regulations regarding ethics and data protection. Therefore, strategic policies and a holistic approach are needed to ensure that the use of AI in education provides optimal benefits while minimizing potential negative impacts.